Pengaruh Deposisi Lapisan Tipis Ti-Al-N Terhadap Umur Pahat Bubut HSS - Nuri, Sigit Hidayat (Semesta Teknika, 2008)
The surface hardness of material can be improved through appropriate technique in surface coating. There are several various techniques have been used in order to obtain an optimum result of surface coating. One of them is sputtering technique. Thin layer deposition of Ti N + Al N (titanium nitride + aluminum nitride) materials with sputtering is a modern coating process for improving material properties. The objective of this paper is to obtain an optimum result on surface hardness of HSS cutting and lifetime cutting tool. The specimen with 9.4 ´ 9.4 ´ 11 mm was coated by Ti-N + Al-N materials in various temperatures, coating times, and gas pressure ratio of Ar and N2.   Hardness test of Micro Vickers was used for 10 gf of load in this study. The optimum hardness number (VHN0,01 1756.2) was reached at 150° C for 2 hours process of pressure ratio of Ar : N2 is 1 : 1 at 3.10-2 kg/cm2. The hardness number of HSS material was found to be 847, 9 VHN0,01. The HSS Ti N + Al N, deposition on HSS cutting tool were used in order to cut medium carbon steel with 1 mm cutting thickness at 0.084 mm/rev of feeding speed. The speed was varied for 35, 45 and 48 m/min. The HSS cutting tool coated by Ti N + Al N has 107 % of hardness and 144% ~ 149 % of life time compared to the uncoated cutting tool.